Bruton's tyrosine kinase regulates TLR9 but not TLR7 signaling in human plasmacytoid dendritic cells. Issue 4 (20th January 2014) - Wang, Jingming; Lau, Kai‐Yeung; Jung, Jimmy; Ravindran, Palanikumar; Barrat, Franck J.
<x xml:space="preserve">Abstract</x> Plasmacytoid dendritic cells (PDCs) represent a key cell type for both innate and adaptive immunity. PDCs express both TLR7 and TLR9 and the recognition of nucleic acids by these two receptors triggers the production of a large amount of type‐I IFN and the induction of PDC maturation into APCs. This unique feature of PDCs is at the basis of clinical development of both TLR7 and TLR9 agonists for infectious diseases, allergy, cancer, and asthma. However, TLR7 and TLR9 recognition of self‐nucleic acids is linked to many autoimmune diseases including lupus, and a better understanding of the signaling pathways of these two receptors in PDCs is thus important. We have identified Bruton's tyrosine kinase (Btk) as an important player for TLR9 but not TLR7 signaling in human PDCs. Blocking Btk using a specific inhibitor leads to the reduction of all TLR9‐induced responses in PDCs, including cytokine production and expression of costimulatory molecules, while this has no impact on the TLR7 response. This identifies Btk as a key molecule in TLR9 signaling in PDCs and is the first demonstration that the TLR7 and TLR9 pathways can be dissociated in human PDCs.